1991
DOI: 10.1113/jphysiol.1991.sp018770
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin activates an inwardly rectifying K+ conductance in freshly dispersed rat somatotrophs.

Abstract: SUMMARY1. Somatotrophs from enzymatically dispersed anterior pituitary glands of rats, enriched to > 94% purity by density gradient centrifugation, were studied within 16 h of isolation using patch clamp recording methods in the conventional whole-cell and the perforated-patch configurations.2. Rhythmic oscillations of membrane potential gave rise to action potentials in thirty-six of fifty-two cells studied with the perforated-patch technique. Membrane potential oscillated between -70 mV and -25 mV with an av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 38 publications
1
50
1
2
Order By: Relevance
“…In other words, these cells are quiescent, and the addition of growth hormone-releasing hormone (GHRH) is required to initiate firing. This is in contrast with the results by Sims et al (20) and Holl et al (21), who observed spontaneous firing of APs and extracellular Ca 2ϩ -dependent fluctuation in [Ca 2ϩ ] i in a fraction of somatotrophs. Several laboratories have also reported that gonadotrophs, lactotrophs, and corticotrophs exhibit periods of spontaneous firing of APs (22)(23)(24)(25).…”
Section: In Excitable Cells Oscillations In Intracellular Free Calcicontrasting
confidence: 56%
“…In other words, these cells are quiescent, and the addition of growth hormone-releasing hormone (GHRH) is required to initiate firing. This is in contrast with the results by Sims et al (20) and Holl et al (21), who observed spontaneous firing of APs and extracellular Ca 2ϩ -dependent fluctuation in [Ca 2ϩ ] i in a fraction of somatotrophs. Several laboratories have also reported that gonadotrophs, lactotrophs, and corticotrophs exhibit periods of spontaneous firing of APs (22)(23)(24)(25).…”
Section: In Excitable Cells Oscillations In Intracellular Free Calcicontrasting
confidence: 56%
“…However, the GABA(B) receptor antagonist CGP 55845 hydrochloride showed no evidence of even a partial block (n ϭ 2, data not shown). HS cells also express SST (Jinno and Kosaka, 2002;Gulyás et al, 2003), a neuropeptide known to signal through GIRK channels (Mihara et al, 1987;Sims et al, 1991) and to evoke similar inhibitory responses in other brain regions (Twery and Gallagher, 1989;Greene and Mason, 1996;Schweitzer et al, 1998), so we hypothesized that the response might be due to SST released by optogenetic stimulation from HS terminals. Indeed, we were able to achieve a partial block (ϳ30%) with the nonspecific SSTR antagonist cyclosomatostatin (5 M; Fig.…”
Section: Fast and Slow Responses In Septal Cells In Response To Hs Inputmentioning
confidence: 99%
“…The most common neuronal action of somatostatin is one of inhibition with its most common cellular mechanism of action being a membrane hyperpolarization brought about by activation of inwardly rectifying potassium channels Inoue, Nakajima & Nakajima, 1988;Lewis & Clapham, 1989;Sims, Lussier & Kraicer, 1991) . This cellular mechanism underlies inhibitory postsynaptic potentials (IPSPs) at several muscarinic, adrenergic and y-aminobutyric acid (GABAB) synapses (Hartzell, Kuffler, Stickgold & Yoshikami, 1977;Dodd & Horn, 1983;Surprenant & North, 1988;Mihara & Nishi, 1989;Nicoll, Malenka & Kauer, 1990); somatostatin might also be expected to mediate similar IPSPs at sites where it is known to be released.…”
Section: Introductionmentioning
confidence: 99%